2010
DOI: 10.1074/jbc.m109.023002
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronyltransferase Activity of KfiC from Escherichia coli Strain K5 Requires Association of KfiA

Abstract: Heparan sulfate is a ubiquitous glycosaminoglycan in the extracellular matrix of most animals. It interacts with various molecules and exhibits important biological functions. K5 antigen produced by Escherichia coli strain K5 is a linear polysaccharide N-acetylheparosan consisting of GlcUA ␤1-4 and GlcNAc ␣1-4 repeating disaccharide, which forms the backbone of heparan sulfate. Region 2, located in the center of the K5-specific gene cluster, encodes four proteins, KfiA, KfiB, KfiC, and KfiD, for the biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The single expression of KfiA or KfiC in E. coli BL21 could not produce heparosan at all, while the co-expression of KfiA and KfiC in recombinant sAC could produce 63 mg/L heparosan in shake flask. It was indicated that the KfiA and KfiC were the only exogenous genes required for heparosan synthesis in E. coli, and this result was consistent with what previously reported (Sugiura et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…The single expression of KfiA or KfiC in E. coli BL21 could not produce heparosan at all, while the co-expression of KfiA and KfiC in recombinant sAC could produce 63 mg/L heparosan in shake flask. It was indicated that the KfiA and KfiC were the only exogenous genes required for heparosan synthesis in E. coli, and this result was consistent with what previously reported (Sugiura et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies of the glycosyltransferases involved in the synthesis of the K5 capsular polysaccharide have demonstrated that protein-protein interactions were essential for activity. In this large transenvelope complex, the glucuronyltransferase activity of KfiC is dependent on physical association with the N-acetylglucosaminyltransferase KfiA (29). Moreover, it has been demonstrated that this complex has a polar localization, consistent with the site where the biosynthesis and export of this polysaccharide occur (17).…”
Section: Discussionmentioning
confidence: 78%
“…The hypothesis that multienzymatic membrane complexes are implicated in the coordination of the biosynthesis (initiation, elongation, and termination) and transport of O polysaccharides and other bacterial polysaccharides is currently being strengthened experimentally (15,17,18,29). Some of these polysaccharides and the lipopolysaccharides (LPS) are important virulence factors in a wide spectrum of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In the related E. coli K5 system, recent studies of glycosyltransferases involved in the synthesis of the K5 capsular polysaccharide found that protein-protein interactions were essential for activity. The glucuronyltransferase activity of KfiC is dependent on physical association with the N-acetylglucosaminyltransferase, KfiA (43). These proteins may be part of a larger trans-envelope complex (44,45).…”
Section: Discussionmentioning
confidence: 99%